La aparición de los signos del tiempo en la animación: una reflexión desde la filosofía del cine de Gilles Deleuze (2017)
Deleuze’s definition of animated cinema in his cinematic studies left open thequestion about whether animation can be considered to be the seventh art. Westart with the fact that animation isn’t just cinema, but that it also makes significantcontributions both in the development of it and in the philosphical discussionsthat arise around it. In order to demonstrate this, we propose a detailed analysisof each one of the signs presented by Deleuze in his book Studies about cinematwo: the image-time (1987) in animated cinema, in order to deepen and rethinkthe work of the French philosopher.